Justice in climate change adaptation planning: conceptual perspectives on emergent praxis. - Fünfgeld, Hartmut; Schmid, Benedikt (Copernicus Publications, 2020)
The measures implemented to adapt to climate change are primarily designed to address the tangible, biophysical impacts of climate change in a given geographic area. They rarely consider the wider social implications of climate change, nor the politics of adaptation planning and its outcomes. Given the necessity of significant investment in adaptation over years to come, adaptation planning and implementation will need to place greater concern on justice-sensitive approaches to avoid exacerbating existing vulnerabilities and creating maladaptive and conflicting outcomes. Building on recent calls for more just and transformative adaptation planning, this paper offers a flexible analytical framework for integrating theories of justice and transformation into research on climate change adaptation. We discuss adaptation planning as an inherently normative and political process linked to issues pertaining to recognition justice as well as distributional and procedural aspects of justice. The paper aims to contribute to the growing discussion on just adaptation by intersecting theoretical justice dimensions with spatial, temporal and socio-political challenges and choices that arise as part of adaptation planning processes. A focus on justice-sensitive adaptation planning not only provides opportunities for examining spatial as well as temporal justice issues in relation to planning and decision-making processes. It also paves the way for a more critical approach to adaptation planning that acknowledges the need for institutional restructuring and offers steps towards alternative futures under climate change conditions.
Keywords: Klimawandel; Klimafolgenanpassung; Raumbezug; Sozialpolitik; Umweltgerechtigkeit; Planung; Forschung